2016
DOI: 10.3390/ma9050337
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanocoating Technology in the Prevention of Prosthetic Joint Infection

Abstract: Prosthetic joint infection (PJI) is a feared complication of total joint arthroplasty associated with increased morbidity and mortality. There is a growing body of evidence that bacterial colonization and biofilm formation are critical pathogenic events in PJI. Thus, the choice of biomaterials for implanted prostheses and their surface modifications may significantly influence the development of PJI. Currently, silver nanoparticle (AgNP) technology is receiving much interest in the field of orthopaedics for it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 288 publications
(251 reference statements)
1
39
0
1
Order By: Relevance
“…Fortunately, the qualitative and quantitative analyses confirmed a concentration-dependent "bactericidal" activity of AgNPs. This type of nanoparticles has exhibited the positive effects on wound healing, suppressing local skin inflammation and preventing pathogens from entering the skin 52,53 . Mechanistically, silver is toxic to many bacterial components such as (i) cell wall where it causes transport blockage and plasma membrane collapse, (ii) enzymatic systems such as respiratory cytochromes, and (iii) microbial DNA and RNA where it prevents transcription and division 54,55 .…”
Section: Morphology Of Agnps Containing Nanofilmsmentioning
confidence: 99%
“…Fortunately, the qualitative and quantitative analyses confirmed a concentration-dependent "bactericidal" activity of AgNPs. This type of nanoparticles has exhibited the positive effects on wound healing, suppressing local skin inflammation and preventing pathogens from entering the skin 52,53 . Mechanistically, silver is toxic to many bacterial components such as (i) cell wall where it causes transport blockage and plasma membrane collapse, (ii) enzymatic systems such as respiratory cytochromes, and (iii) microbial DNA and RNA where it prevents transcription and division 54,55 .…”
Section: Morphology Of Agnps Containing Nanofilmsmentioning
confidence: 99%
“…As the attachment of bacteria to indwelling devices depends at least partially on the properties of the device surface, optimization of device polymer chemistry or coating with antiadhesive or antibacterial compounds, such as metal ions (silver, copper, zinc), and nanoparticle technology have been used (Swartjes et al, 2015;Gallo et al, 2016). However, these strategies have not had complete clinical success, most likely due to the fact that the devices are covered by human matrix proteins largely independently of their chemistry, an effect also prone to diminish the efficacy of device surfaceattached antibacterials.…”
Section: Strategies For the Development Of Drugs For The Treatment Ofmentioning
confidence: 99%
“…Romano et al divided antibacterial coatings of the implants into three groups: (1) passive surface modification that prevents biofilm formation; (2) active surface modification that contains pharmacologically active bactericidal agents (that is, metals or non‐metal elements, organic substances); and (3) local carriers or coatings that are applied at the time of the surgical procedure. Antibacterial coatings employing metals (i.e., silver, copper, zinc) proved to be an effective and cost‐effective strategy in reducing the risk of infectious complications…”
Section: Introductionmentioning
confidence: 99%
“…While many studies demonstrated clinical efficacy and safety of the implication of the silver‐coated implants, recent reports suggest that silver may negatively affect patient health…”
Section: Introductionmentioning
confidence: 99%